Insights on Bubbling Formation after Drop Impact on Thin Liquid Films - Ribeiro, Daniela (2020)
Over the years, the phenomena obtained when a drop impinges upon a dry, wetted or heated surface have been thoroughly studied. In previous works, the existence of splash was investigated by the authors with the goal of evaluating the possible implementation of biofuels in the civil aviation and it was found an episode of a phenomenon, seldom reported in the literature under specific pre-impingement conditions. The mechanism that leads to a bubble formation has two stages. After the drop impacts a steady liquid film, prompt splash occurs followed by crown splash. In the first stages of crown splash, the uprising sheet propagates almost normal to the liquid film, but its radius at the base continues to expand, eventually leading to the inward collapse of the crown bounding rim. Thus, the top of the crown closes in a bubble-like shape with the formation of two jets, one upwards and other downwards. The upward jet eventually disappears due to gravitational influence, while the downward jet continues to grow until it reaches the liquid film, attaching to it, stretching and detaching from the top at the hemispheric thin-sheet, forming a perfect bubble. Many secondary droplets fall on the bubble and one of them will eventually break the dome, leading to more secondary atomization. The few works reported in the literature referring to this phenomenon as “bubbling” or “floating bubble,” scarcely explore the hydrodynamic mechanism associated with this bubble formation and occurrence, mainly focusing on droplets impacting upon deep pools. However, in a previous study, the authors observed this event for a liquid film dimensionless thickness of 0:5 in a fluid mixture of Jet A-1 and biofuel NEXBTL. In this study, the impact conditions in the experiments performed allow to recreate the floating bubble with 100% of occurrence. After that, the authors present an extensive characterization of the bubbling phenomenon to understand better the mechanisms which lead to its formation, as well as its practical significance. A high-speed digital camera acquires several images of the floating bubble formation from different points of view (side and bottom). Namely, capturing the phenomenon from below, high-quality images allow retrieving essential data to describe the hydrodynamic mechanism accurately. The most relevant features include the bubble height and diameter, and the propagation velocity of the first perturbation imposed on the liquid film.